Extended alone and ignore assessments: A novel examination of factors that influence determination of an automatic function. (10th March 2022) - Bottini, Summer; Stremel, J. Meredith; Scheithauer, Mindy; Morton, Hannah E.
Abstract: When targeted behaviors are hypothesized to be automatically maintained, an extended assessment is often necessary to evaluate the impact of social contingencies and guide intervention selection. Elements that may be related to determining assessment outcome include observed characteristics of the behavior, type of sessions conducted, and the topography of targeted behavior. The present retrospective chart review analyzed these variables in 51 clients with developmental disabilities who were exposed to extended alone or ignore evaluations as part of a clinical admission. Findings indicate clinicians may conduct more sessions during extended assessments than previously reported. Level of behavior and pica as the presenting topography primarily drove determination of an automatic function. Session type and other topographies were not statistical predictors of assessment outcome. We discuss these findings with respect to balancing internal and social validity. We also present exploratory and statistically derived cut offs to consider when assessment length is constrained.